Influence of Border-Keepers’ Support on Work-Family Enrichment of Preschool Teachers in China: The Mediating Role of Work-Family Boundary Flexibility - Peng, Qian; Lian, Chongyan; Zhang, Limin (Frontiers in Psychology, 2022)
Based on accumulation/ enrichment of resource theory and work/family border theory, this paper examines the impact of border keepers’ supports (Organizational support and family support) on work-family enrichment and whether and how work/family boundary flexibility mediates the relationship between border keepers’ supports and work-family enrichment. A sample of 504 preschool teachers in China from Guangdong province completed questionnaires. The research results show a two-way process of work-family enrichment for preschool teachers in China. Organizational support was directly and significantly correlated with work-to-family enrichment, and family support was significantly and directly correlated with family-to-work enrichment. Organizational support had no significant positive predictive effect on work flexibility-ability which has a significant positive predictive effect on work-to-family enrichment. In addition, the study found that work boundary flexibility did not act as a mediating factor between organizational support and work-to-family enrichment. Family support had a significant positive predictive effect on family flexibility-ability which had a significant positive predictive effect on the family-to-work enrichment. Family boundary flexibility mediates the relationships between family support and family-to-work enrichment. The above research results are partly consistent with the existing research, and partly inconsistent, which is related to the profound influence of Confucian culture in Chinese society and the current situation of preschool teachers in China.